Environmental Accounting: Evaluation and Reporting of Carbon Footprint in the Energy Sector - Kurniawan, Agus; Restie Utami, Zathu (FIDUSIA : JURNAL KEUANGAN DAN PERBANKAN, 2025)
The growing concern over climate change has intensified the need for organizations to manage and report their carbon footprints, particularly in the energy sector. This study explores the role of environmental accounting in evaluating and reporting carbon footprints, focusing on the energy industry's practices. It examines the current methodologies for measuring carbon emissions, challenges in implementing accurate reporting systems, and the regulatory frameworks driving accountability. By analyzing case studies from different energy companies, this research highlights best practices and areas for improvement in environmental accounting processes. The findings suggest that a more standardized approach to carbon reporting can enhance transparency and contribute to global sustainability goals. Additionally, the study proposes strategies for integrating carbon accounting into corporate governance frameworks to better align environmental performance with financial reporting. The results underscore the importance of robust environmental accounting practices in reducing carbon footprints and fostering long-term environmental stewardship within the energy sector.